Kalimat Teks Eksposisi Karya Siswa Kelas VIII SMP - Hendrisman Hendrisman; Sri Mures Walef (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2021)
This study aims to describe the structure of single sentence patterns of seventh-grade students of SMPN 1 Guguak, Lima Puluh Kota Regency. This type of research uses descriptive qualitative. The object of this research is a student worksheet in the form of an exposition text, with the research subject being the students of SMP N 1 Guguak, Lima Puluh Kota Regency. The results showed 89 data elements in a single sentence pattern in the exposition text of class VIII students of SMP N 1 Guguak, Lima Puluh Kota Regency. The sentence structure with the S + P pattern consists of 2 data (2%), the use of the S + P + O pattern element is 17 sentences from 89 data (19%), the use of the S + P + Pel pattern element is 20 sentences from 89 data (24%), the use of the S+P+Ket pattern element contained 15 sentences from 89 data (7%), the use of the S+P+O+Pel pattern element contained 18 sentences from 89 data (22.5%), and the S sentence element pattern +P+O+Ket there are 17 sentences from 89 data (18%). In conclusion, the most widely used single sentence pattern element in the exposition text of VIII grade students of SMP N 1 Guguak, Lima Puluh Kota Regency is the S+P+Pel pattern. Keywords: Sentence Pattern Structure, Exposition Text